Therapeutic strategies in cancer biology and pathology - Sherbet, G. V. (Gajanan V.) (Elsevier insights., 2013)
Currently, intensive effort is being directed toward the identification of molecular targets that can provide approaches to the development of novel therapeutic strategies in cancer management. This book focuses on metastasis-associated genes, metastasis promoter and suppressor genes, which relate specifically to behavioral alterations of cancer cells in epithelial mesenchymal transition, cancer stem cell maintenance and propagation, and to the acquisition of invasive and metastasis faculty. The function of these genes has implications for cell cycle regulation and cell proliferation and so constitute an essential element in cancer growth and dissemination.